Ileal obstruction caused by an intact “Shine Muscat” grape: a case report - Kuanyong Yu; Wenjun Feng; Guanghui Qiang; Chuanyang Cao; Liyang Liu; Zhenling Ji (Frontiers in Medicine)
IntroductionThis case report presents a rare instance of small-bowel obstruction (SBO) caused by an intact “Shine Muscat” grape, highlighting the importance of considering unusual foreign bodies in the differential diagnosis of SBO, especially in the elderly.Case descriptionAn 87-year-old edentulous female presented with a 2-day history of abdominal pain, bloating, vomiting, and constipation. Abdominal computed tomography (CT) scan revealed SBO with a foreign body in the ileum. The patient confessed swallowing an intact grape 2 days prior to admission. Surgery was performed, and an intact green grape was extracted from the dilated ileum, relieving the obstruction. This case highlights the rare case of SBO caused by an intact grape and underscores the importance of a detailed dietary history in the diagnosis of SBO. The use of CT scanning was instrumental in identifying the grape as the cause of obstruction. Early surgical intervention led to a successful outcome, emphasizing the need for prompt action in managing such cases.